Revised genetic diagrams for natural gases based on a global dataset of >20, 000 samples. (November 2018) - Milkov, Alexei V.; Etiope, Giuseppe
Highlights: Revised genetic diagrams for natural gases based on 20, 621 samples. Early mature thermogenic gas may have methane depleted in 13 C (δ 13 C around −75‰). Late mature thermogenic gas has methane enriched in 13 C (δ 13 C around −15‰). The values of δ 13 C of abiotic methane can be as negative as −50‰. Many natural gases are mixtures; integration is key for robust interpretation. Abstract: The origin of natural gases, in particular those containing methane (CH4 or C1 ), ethane (C2 H6 or C2 ), propane (C3 H8 or C3 ) and carbon dioxide (CO2 ), is commonly interpreted using binary genetic diagrams of δ 13 C-C1 versus C1 /(C2 + C3 ), δ 13 C-C1 versus δ 2 H-C1 and δ 13 C-C1 versus δ 13 C-CO2 . These diagrams are empirical, but their currently used genetic fields were proposed around 30–40 years ago based on geographically and geologically limited datasets of tens to few hundreds gas samples. As a result, many recently collected gas samples plot outside of accepted genetic fields making these genetic diagrams partly inadequate for the purpose of gas interpretation. Here, we update the genetic diagrams using geochemical and geological data on 20, 621 gas samples from a variety of geographical areas (76 countries and territories on six continents) and geological habitats (conventional and unconventional petroleum reservoirs, petroleum seeps and mud volcanoes, gas hydrates, volcanic/geothermal/hydrothermal manifestations, seeps and groundwater in serpentinized ultramafic rocks, aquifers, freshwater and marine sediments, igneous and metamorphic rocks). The revision includes genetic fields for primary microbial gases from CO2 reduction and methyl-type fermentation, secondary microbial gases generated during petroleum biodegradation, thermogenic and abiotic gases. The genetic field of thermogenic gases now includes early mature ( δ 13 C-C1 as low as −75‰) and very late mature ( δ 13 C-C1 around −15‰) gases recently recognized in various petroleum systems. Abiotic C1 is not necessarily 13 C-enriched ( δ 13 C > −20‰) as was often considered in the past. The δ 13 C values of abiotic C1 can be as negative as around −50‰, although a minor component of biotic (microbial or thermogenic) C1 is often associated with abiotic gas. In addition, the diagrams display molecular and isotopic changes that accompany post-generation processes of mixing, migration, biodegradation, thermochemical sulphate reduction and oxidation. The proposed diagrams cover the vast majority of hydrocarbon-containing gases currently known to exist in nature, are the most comprehensive empirical gas genetic diagrams published to date, and thus represent an essential tool for interpretations of natural gases. Still, holistic integration of geochemical and geological data is necessary to better interpret the origin of natural gases and processes that affected their composition.